Two-handed Input in a compound task - Kabbash, Paul; Buxton, Bill; Sellen, Abigail (Proceedings of CHI'94, Boston, MA, 1994)
Four techniques for performing a compound drawing/color selection task were studied: a unimanual technique, a bimanual technique where different hands controlled independent subtasks, and two other bimanual techniques in which the action of the right hand depended on that of the left hand. We call this latter class of two-handed technique “asymmetric dependent,” and predict that because tasks of this sort most closely conform to bimanual tasks in the everyday world, they would give rise to the best performance. Results showed that one of the asymmetric bimauual techniques, called the Toolglass technique, did indeed give rise to the best overall performance. Reasons for the superiority of this technique are discussed in terms of their implications for design. These are contrasted with other kinds of two-handed techniques, and it is shown how, if designed inappropriately, two hands can be worse than one.